Subgenomic flavivirus RNA (sfRNA) associated with Asian lineage Zika virus identified in three species of Ugandan bats (family Pteropodidae) - Fagre, Anna C.; Lewis, Juliette; Miller, Megan R.; Mossel, Eric C.; Lutwama, Julius J.; Nyakarahuka, Luke; Nakayiki, Teddy; Kityo, Robert; Nalikka, Betty; Towner, Jonathan S.; Amman, Brian R.; Sealy, Tara K.; et al. (Scientific reports, 2021)
Serological cross-reactivity among flaviviruses makes determining the prior arbovirus exposure of animals challenging in areas where multiple flavivirus strains are circulating. We hypothesized that prior infection with ZIKV could be confirmed through the presence of subgenomic flavivirus RNA (sfRNA) of the 3′ untranslated region (UTR), which persists in tissues due to XRN-1 stalling during RNA decay. We amplified ZIKV sfRNA but not NS5 from three experimentally-infected Jamaican fruit bats, supporting the hypothesis of sfRNA tissue persistence. Applying this approach to 198 field samples from Uganda, we confirmed presence of ZIKV sfRNA, but not NS5, in four bats representing three species: Eidolon helvum (n = 2), Epomophorus labiatus (n = 1), and Rousettus aegyptiacus (n = 1). Amplified sequence was most closely related to Asian lineage ZIKV. Our results support the use of sfRNA as a means of identifying previous flavivirus infection and describe the first detection of ZIKV RNA in East African bats.
Keywords: Subgenomic flavivirus RNA (sfRNA); Asian lineage Zika virus; Ugandan bats (family Pteropodidae)